The Effect Of Work Motivation And Good Corporate Governance With Employee Engagement As An Intervening Variable On The Performance Of Employees Of PT. Luky Tex Indonesia Semarang - Winti Windrati; Samtono Samtono; Andhi Supriyadi (International Conference On Digital Advanced Tourism Management And Technology, 2023)
An important aspect that determines whether firm goals are attained through employee performance is human resources, or labor. Through employee engagement, this study seeks to investigate and explain how job motivation and sound corporate governance affect employee performance. The study was carried out utilizing quantitative techniques. PT. Luky Tex Indonesia Semarang's 90 employees were chosen at random as a sample for this study. The method for gathering the data involved a questionnaire, and Path Analysis with SPSS version 25 was used to evaluate and analyze the results. Results of this study that work motivation and Good Corporate Governance affect employee engagement of PT. Luky Tex Indonesia Semarang. Work motivation, Good corporate governance and Employee engagement affect the performance of PT. Luky Tex Indonesia Semarang. Employee engagement mediates the effect of work motivation and good corporate governance on the performance of PT. Luky Tex Indonesia Semarang